Development of a Smoke-Free Homes Intervention for Parents: An Intervention Mapping Approach. (19th December 2019) - O'Donnell, Rachel; Dobson, Ruaraidh; de Bruin, Marijn; Turner, Stephen; Booth, Lorna; Semple, Sean
Exposure to second-hand smoke (SHS) is associated with various ill-health outcomes for children and adults. Barriers to creating a smoke-free home (SFH) are well-documented. Feasible and effective interventions to create smoke-free homes for disadvantaged households are lacking. Interventions that include providing parents with objective information about the impact of smoking on air quality in their home may be particularly effective. This study describes the development of a novel, theory- and evidence-based smoke-free homes intervention using objectively-assessed air quality feedback. The intervention was developed using the six-step Intervention Mapping (IM) protocol. Findings from literature reviews, focus groups with parents, interviews with health/care professionals, and expert panel discussions shaped intervention content and materials. Findings highlighted the importance of parents receiving personalised information on second-hand smoke levels in their home. Professionals considered the use of non-judgemental language essential in developed materials. Previous literature highlighted the need to address home smoking behaviour at a household rather than individual level. The AFRESH intervention is modular and designed to be delivered face-to-face by healthcare professionals. It includes up to five meetings with parents, two sets of five days' air quality monitoring and personalised feedback, and the option to involve other household members in creating a smoke-free home using educational, motivational, and goal setting techniques. Further research is needed to evaluate the acceptability and effectiveness of the AFRESH intervention and which specific groups of parents this intervention will most likely benefit. IM was a useful framework for developing this complex intervention. This paper does not present evaluation findings.